2016
DOI: 10.3390/ijms17050627
|View full text |Cite
|
Sign up to set email alerts
|

New Concepts in Cancer Biomarkers: Circulating miRNAs in Liquid Biopsies

Abstract: The effective and efficient management of cancer patients relies upon early diagnosis and/or the monitoring of treatment, something that is often difficult to achieve using standard tissue biopsy techniques. Biological fluids such as blood hold great possibilities as a source of non-invasive cancer biomarkers that can act as surrogate markers to biopsy-based sampling. The non-invasive nature of these “liquid biopsies” ultimately means that cancer detection may be earlier and that the ability to monitor disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
188
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(192 citation statements)
references
References 442 publications
3
188
0
1
Order By: Relevance
“…2 Recent literatures showed that exosomes are closely related to tumor development and metastasis and even influence the therapeutic effect in cancer patients. 6,7 The stable presence of miRNAs in body fluids is partly because they are packed into microvesicles or exosomes. 8 Besides, miRNAs and mRNAs in exosomes are functional.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent literatures showed that exosomes are closely related to tumor development and metastasis and even influence the therapeutic effect in cancer patients. 6,7 The stable presence of miRNAs in body fluids is partly because they are packed into microvesicles or exosomes. 8 Besides, miRNAs and mRNAs in exosomes are functional.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, mutation can be missed in cases of contamination, widespread necrosis, or when only small quantities of DNA are available [153]. Perhaps for the same reason, there is a lack of consistent and robust results of circulating genomic materials, with many apparently contradictory reports in the literature [154]. Lee and group [107] found one of their patients had all COSMIC mutations though the patient was negative for EpCAM-positive CTCs.…”
Section: Limitationsmentioning
confidence: 99%
“…Perfect complementarity between miRNA and mRNA leads to cleavage and degradation of the latter, whereas imperfect complementarity results into suppression of the translation of the target mRNA (Tang 2005). Otherwise, mature miRNAs can be secreted by cells in biological fluids including plasma, serum, saliva and several other body fluids (Larrea et al 2016). miRNAs can be released by passive secretion from cells that lost their integrity after tissue injury, cell apoptosis or necrosis (Laterza et al 2009).…”
Section: Part 2 Micrornasmentioning
confidence: 99%
“…An alternative hypothesis is that miRNAs are actively secreted from cells in microvesicles such as exosomes or shedding vesicles (Valadi et al 2007) (Mohammadian et al 2013). NGS is used to detect both novel and known miRNAs, with the limit that this technique is relatively expensive (Larrea et al 2016). Finally, ISH technology may provide information regarding the exact localization of miRNAs within the tumor cell itself or within tumor stromal cells (Nuovo 2010), but has limited relevance as to circulating miRNAs are concerned.…”
Section: Part 2 Micrornasmentioning
confidence: 99%